Adverse Psychosexual Impact Related to the Treatment of Genital Warts and Cervical Intraepithelial Neoplasia. (24th March 2013) - Campaner, Adriana Bittencourt; Vespa Junior, Nelson; Giraldo, Paulo César; Leal Passos, Mauro Romero
Abstract : Objective . To compare the psychosexual impact related to the treatment of genital warts and cervical intraepithelial neoplasia (CIN) in women. Methods . 75 patients presenting with HPV-induced genital lesions, belonging to one of two patient groups, were included in the study: 29 individuals with genital warts (GWs) and 46 individuals with CIN grades 2 or 3 (CIN 2/3). Initially, medical charts of each woman were examined for extraction of data on the type of HPV-induced infection and treatment administered. Subjects were interviewed to collect sociodemographic data as well as personal, gynecologic, obstetric, and sexual history. After this initial anamnesis, the Sexual Quotient-Female Version (SQ-F) questionnaire was applied to assess sexual function. After application of the questionnaire, patients answered specific questions produced by the researchers, aimed at assessing the impact of the disease and its treatment on their sexual lives. Results . It is noteworthy that patients with CIN 2/3 had statistically similar classification of sexual quotient to patients with GWs (P = 0.115 ). However, patients with GWs more frequently gave positive answers to the specific questions compared to patients with CIN 2/3. Conclusion . Based on these findings, it is clear that GWs have a greater impact on sexual behavior compared to CIN 2/3.